Analisis Determinan Kualitas Laporan Keuangan Pada Dinas Pekerjaan Umum Dan Penataan Ruang Pemerintah Provinsi Sumatera Utara - Tengku Dewi Rahmadani; Debbi Chyntia Ovami (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The North Sumatra provincial government's public works and spatial planning department is a government agency which operates in the field of building, maintaining, checking and controlling roads in North Sumatra. This research aims to determine the influence of human resource competence, use of information technology and internal control systems on the quality of the financial reports of the public works department and spatial planning of the North Sumatra provincial government. This research uses a quantitative approach method with the type of data used in this research using primary data by distributing questionnaires to 36 respondents as a data collection tool, the data analysis used in this research uses multiple linear regression analysis, the population used in this research is staff of the finance department of the public works and spatial planning department of the North Sumatra provincial government. The results of the research show that human resource competence in the use of information technology and internal control systems has a positive and significant effect on the quality of financial reports. Keywords: HR Competency, Information Technology, Internal Control, Quality of Financial Reports.